Pengaruh Implementasi Forced Distribution Rating Performance Appraisal terhadap Task Performance: Motivasi dan Retensi sebagai Mediasi - Hidayat, Dimas Andi Satriyoadi; Sari, Juwita; Sridadi, Ahmad Rizki (Fakultas Ekonomi Universitas Samudra, 2022)
The assessment method of human resource that is often used, but has not been widely discussed in empirical studies is the Forced Distribution Rating Performance Appraisal (FDRPA). This study examines the effect of FDRPA on task performance mediated by motivation and retention. Data from Relationship Managers at a bank in Surabaya that implements the FDRPA system. Data collect is 81 people. The results show that FDRPA has a positive effect on task performance. Where, motivation and retention also show the mediating role of the relationship between FDRPA on task performance. This shows that management needs to understand that the factors in improving the performance of the task, there are variable motivation and retention that need to be considered as well. Furthermore, management is expected to be able to manage the implementation of FDRPA well, so that these positive benefits can continue to be sustainable.